2016
DOI: 10.1016/j.fcr.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Yield gaps in rice-based farming systems: Insights from local studies and prospects for future analysis

Abstract: The important contribution of rice to global food security requires an understanding of yield gaps in rice-based farming systems. However, estimates of yield gaps are often compromised by a failure to recognize the components that determine them at a local scale. It is essential to define yield gaps by the biological limitations of the genotype and the environment. There exist a number of methods for estimating rice yield gaps, including the use of crop growth simulation models, field experiments and farmer yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 74 publications
3
64
2
1
Order By: Relevance
“…In terms of cost and benefit, FWM practices in the wet season could be more economical than the 3 "hand weedings" in BWM plots if combined with the rodent management. The average yield, however, during the wet season (3.1 ± 0.10 t/ha) in our study was lower than the optimum yield of 5 t/ha reported by Stuart et al (2016). Other crop management practices, such as crop 406 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 nutrition, may also need to be improved to achieve such yield levels.…”
Section: Season (1) Treatment (2) Treatmentcontrasting
confidence: 91%
“…In terms of cost and benefit, FWM practices in the wet season could be more economical than the 3 "hand weedings" in BWM plots if combined with the rodent management. The average yield, however, during the wet season (3.1 ± 0.10 t/ha) in our study was lower than the optimum yield of 5 t/ha reported by Stuart et al (2016). Other crop management practices, such as crop 406 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 nutrition, may also need to be improved to achieve such yield levels.…”
Section: Season (1) Treatment (2) Treatmentcontrasting
confidence: 91%
“…The exploitable yield gap of a crop grown in a certain location and cropping system is defined as the difference between the yield under optimum management and the average yield achieved by farmers [32]. The exploitable yield gap is described as a percentage by dividing this value by the yield under optimum management.…”
Section: Yield Gap Between Bmp and Farmer's Practicementioning
confidence: 99%
“…In this study, we find that extensive and diversified management methods are the main reasons for the difference in yield between different farmers' fields and experimental stations, such as excessive rates of fertilizer application, unreasonable fertilization methods, high sowing rate, unsuitable sowing date, and mixed varieties. To understand farmers' actual yield limitations well, the fertilizer use, planting date, variety, and other factors should be taken into account [30]. The actual yield is usually much smaller than other kinds of yields, so it is advocated by the majority of researchers to grope for the restricting factors to actual yield in order to decrease yield gap in farmers' fields [31][32][33].…”
Section: Yield Gaps and Their Limiting Factorsmentioning
confidence: 99%